Broadcasting Algorithms of Three-Dimensional Petersen-Torus Network - Jong-Seok Kim; Hyeong-Ok Lee; Mihye Kim; Sung Won Kim (Journal of Applied Mathematics)
The three-dimensional Petersen-torus network 3PT is based on the Petersen graph and has recently been proposed as an interconnection network. 3PT is better than the well-known 3D torus and 3D honeycomb mesh in terms of diameter and network cost. In this paper, we propose one-to-all and all-to-all broadcasting algorithms for 3PT(l;m;n) under SLA (single-link available) and MLA (multiple-link available) models.